DEVELOPMENT OF POP UP BOOK MEDIA WITH AUGMENTED REALITY FEATURES IN IMPROVING STUDENTS' CREATIVE WRITING SKILLS IN ELEMENTARY SCHOOLS - Raihani Afifah; Moh. Farizqo Irvan; Lavia Zahra Sabila; Dian Apriliya Andriyani; Adreng Sayekti; Putri Nur Aurora; Anggian Ristianto (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
In the current era of disruption, the competencies needed for the 21st century are no longer just 4C but are developing into 6C. However, Indonesia's PISA scores from 2012, 2015 and 2018 show very fluctuating numbers so it needs to be improved. Referring to competence, namely creativity, it can be improved one way or another through creative writing skills supported by effective learning media. This study aims to develop and test the feasibility of the Pop-Up Book media with the Augmented Reality feature in improving the creative writing skills of elementary school students. The subject in this study is the assessment of media and material practitioners. This study uses the ADDIE model RnD development method. Data collection techniques used are observation, interviews, questionnaires, and scoring. The instrument used in the scoring stage is a validation sheet from media and material experts. The data analysis technique used in this study is a quantitative data analysis technique. The results of the validation and assessment of media and material practitioners, the score obtained from media experts is 70% in the appropriate category and the score from material experts is 85% in the very feasible category. Thus, it can be concluded that the Pop-Up Book media with the Augmented Reality feature is ready and very feasible to be used by teachers and students as an alternative solution in supporting the creative writing skills of elementary school students. Future researchers should be able to use the results of this study as a basis for testing the effectiveness of the Augmented Reality Pop-Up Book media feature in improving elementary school students' writing skills.